An exhaustive review of studies on natural convection in enclosures with and without internal bodies of various shapes. (August 2019) - Pandey, Sudhanshu; Park, Yong Gap; Ha, Man Yeong
Highlights: Review on numerical and experimental studies pertaining to natural convection in enclosures. Effect of internal bodies such as square, circular and elliptical cylinder on flow mechanism. Summarization of different methodologies used to improve the thermal behavior of buoyancy driven flows within an enclosure. Effect of wall boundary conditions, position and number of internal bodies. Categorization of flow regimes and the factors affecting the transition from steady to unsteady state. Abstract: Natural convection has been extensively studied due to its presence in many engineering applications. It is one of the most important modes of heat transfer and arises due to buoyancy-induced flows resulting from temperature differences. This review presents a detailed summary of numerical and experimental studies related to laminar natural convection in enclosures with and without internal bodies. Square, circular, and elliptical cylinders are mostly considered as internal bodies. The presence of internal bodies makes significant changes in the flow characteristics within the enclosure. The effects on the flow regime and thermal fields of various parameters have been discussed in detail, including the Rayleigh number, aspect ratio, position of internal bodies, number of internal bodies, and inclination angle. The different flow regimes depending on the input parameters are categorized based on observations made from flow and thermal patterns. This review discusses various methodologies used by a large group of researchers to improve the hydrodynamic and thermal behavior for buoyancy-driven flows within an enclosure.